2006
DOI: 10.1016/j.livsci.2006.03.017
|View full text |Cite
|
Sign up to set email alerts
|

Hygienic and ecological risks connected with utilization of animal manures and biosolids in agriculture

Abstract: In recent years the fate of human and animal pathogen microorganisms as a potential pollutant of the environment has been paid increased attention. Substantial quantities of these compounds and their metabolites are excreted, flushed down the drain, discarded as waste, or left over in animal feedlots. After passing to the sewer, several of these compounds are not adequately eliminated by the methods that are currently used in sewage treatment. Substantial quantities of biosolids and livestock manure end up on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
46
1
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 15 publications
1
46
1
6
Order By: Relevance
“…Analogical regularity was observed in the study by Venglovsky et al (2006), who also claim that apart from the temperature, the factors which considerably affect the elimination rate of invasive eggs from the given environment are: the type of slurry or soil, relative humidity and UV radiation. Reports of those authors (Venglovsky et al, 2006), similarly to the results of the present study, indicated that parasite eggs subjected to the environmental factors lose their invasiveness, but this process lasts long enough for them to be able to induce infections in people and animals. Slurry is the most important medium contributing to transmission of A. suum eggs from animals having ascariasis to the environment.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Analogical regularity was observed in the study by Venglovsky et al (2006), who also claim that apart from the temperature, the factors which considerably affect the elimination rate of invasive eggs from the given environment are: the type of slurry or soil, relative humidity and UV radiation. Reports of those authors (Venglovsky et al, 2006), similarly to the results of the present study, indicated that parasite eggs subjected to the environmental factors lose their invasiveness, but this process lasts long enough for them to be able to induce infections in people and animals. Slurry is the most important medium contributing to transmission of A. suum eggs from animals having ascariasis to the environment.…”
Section: Discussionsupporting
confidence: 76%
“…Eggs of A. suum are regarded as the most resistant to unfavourable environmental conditions, where they can survive for months, and even for years (Crompton, 2001). A. suum eggs may occur in all types of environments, but the main source of their transmission is the agricultural usage of swine slurry for fertilization, its transport and spray irrigation after previous dilution (Crompton, 2001;Venglovsky et al, 2006). Especially high risk is found in the vicinity of large pig farms (Caballero-Hernández, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…There are significant microbiological risks related to animal wastes spread onto land subsequently used for crop production or livestock grazing (Lauková et al, 2000;Burton & Turner, 2003). Unsuitable manipulation, too short or too long storage and intensive use of excrements particularly in the immediate surroundings of farms may frequently result in environmental pollution with respect to noxious gasses and odours, contamination of surface and ground water and hygiene risks related to micro-organisms and various parasitic stages (Nicholson et al, 2005;Venglovský et al, 2006Venglovský et al, , 2009Papajová & Juriš, 2009). People are in constant contact with soil either directly or indirectly through food, water or air.…”
Section: Introductionmentioning
confidence: 99%
“…Because wastewater generated by the swine industry can contain high parasite loads (VENGLOVSKÝ et al, 2005) and can be reused, previous studies have shown the need to establish limits regarding the presence of viable helminth eggs as a preventive control measure (TOPP et al, 2009). However, more data are needed to strengthen the case for using the proposed parameters as legal requirements in sewage sanitary control (SALGOT et al, 2006).…”
Section: Introductionmentioning
confidence: 99%